Avaliação dos efeitos de drogas anti-adenosinérgicas e do disseleneto de difenila no prejuízo da memória e estresse oxidativo relacionados ao envelhecimento - Leite, Marlon Regis (2012)
Biological aging is gradual and progressive decline of physical functions that begin in adulthood and ends with death in almost all animals species. One of the most common features of aging is the reduced ability to learn and remember new information. Age-related changes in the neural basis of memory processes are closely linked to oxidative stress. Here, the effects of caffeine caffeine and SCH58261, an A2A receptor antagonist, in the memory impairment and oxidative stress influenced by age in rats were investigated. Young and old rats were treated daily for 10 days with caffeine (30 mg/kg, p.o.) or SCH58261 (0,5 mg/kg, p.o.). The test used to evaluate the memory of animals was the novel object recognition task (article 1). After behavioral tasks, ascorbic acid and oxygen and nitrogen reactive species levels as well as Na+K+ ATPase activity were determined in rat brain. The results showed that memory deficit influenced by age was reversed by treatment with caffeine or SCH58261 besides improving short-term memory. Young animals also showed improved memory for short and long term when treated with caffeine and SCH58261.Furthermore, increased oxygen and nitrogen reactive species levels in brain of old rats were normalized by both caffeine and SCH58261. However, ascorbic acid levels decreased in brain of old rats were not changed by CAF or SCH58261. The inhibition Na+K+ ATPase activity in brain of old rats was also normalized by caffeine and SCH58261. Since caffeine ameliorates memory of aged rats and taking into account that organoselenium compounds have antioxidant and neuroprotective properties, it was also investigated whether diphenyl diselenide (PhSe)2 compound could improve memory impairment in middle-aged rats in a model of supplementation with caffeine. Middle-aged rats were treated for 30 days with both (PhSe)2 (10 p.p.m. in feed) and caffeiene (15 mg/kg, o.p.) or only (PhSe)2 or caffeine. Memory of animals was evaluated in the novel object recognition task (manuscript 1). The results showed an improvement in the short-term memory in animals treated only with (PhSe)2. The long-term memory was improved only in animals treated with both (PhSe)2 and caffeine. Moreover, treatments affected locomotor and exploratory activity. Thus, this study suggests that both antagonists of adenosinergic receptor, and (PhSe)2 were effective in ameliorating memory impairment influenced by aging.